COMPARISON ANALYSIS OF INFLUENCE OF CURRENT RATIO ON FINANCIAL PERFORMANCE - Irman Firmansyah (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2017)
ABSTRACTThis study aims to determine the effect of liquidity on corporate financial performance. One of the financial ratios used to measure short-term liquidity is Current ratio. While some financial ratios that can be used to measure financial performance are return on asset, return on equity and gross profit margin. This research was conducted at companies listed in Jakarta Islamic Index (JII) in the period of 2015 and 2016. The analysis tool used is a simple regression with analysis of 3 times to all financial ratios of financial performance. The analysis shows that current ratio does not affect the financial performance of both return on assets, return on equity and gross profit margin.Keywords: Current ratio, financial performance, jakarta islamic index